A Mixed-Methods Study of Cultural Heritage Learning through Playing a Serious Game - Kara, Nuri (Taylor & Francis Inc, 2024)
The main goal of this study was to investigate the impact of a serious game on university students' learning about cultural heritage content and to reveal the factors affecting their learning experiences during the serious gameplay. The serious computer game Europe in a museum, which includes tangible and intangible cultural heritage visuals of several European countries, was used in the study. The main research design was a mixed-methods sequential explanatory design. The participants were 50 freshman students studying in the Digital Game Design department at a private university. Pre-knowledge test, post-test and delayed post-test instruments were used to collect quantitative data, while semi-structured interviews were implemented to obtain qualitative data. Based on independent-measures t-tests, post-test and delayed post-test scores of the students' cultural heritage knowledge for students who played the serious game were significantly higher than those of students taught by traditional methods. Content analysis results showed that game design, gameplay and instructional content were the main themes affecting players' learning experiences during the serious gameplay. According to the students, the narrative used to convey the story of the game created a better playing and learning experience. The students indicated that the challenges must be consistent with the expectations of the gamers. They also noted that concise and clear presentation of cultural heritage content within the game had a positive impact on their learning experiences. This study contributes to the literature in showing the long-term effect of serious games on cultural heritage learning. Factors influencing the cultural heritage learning experience of players during serious gameplay can be a guide for instructors, instructional technologists and game designers.
Keywords: Gamification; Design